Significant improvements, but consistent disparities in survival for African Americans after liver transplantation. Issue 6 (25th March 2022) - Keeling, Stephanie S.; McDonald, Malcolm F.; Anand, Adrish; Handing, Greta E.; Prather, Lyndsey L.; Christmann, Caroline R.; Jalal, Prasun K.; Kanwal, Fasiha; Cholankeril, George; Goss, John A.; Rana, Abbas
Abstract: Despite improvements in survival across races in the past 20 years, African Americans have worse liver transplant outcomes after orthotopic liver transplantation (OLT). This study aims at quantifying the change in disparities between African Americans and other races in survival after OLT. We retrospectively analyzed the United Network for Organ Sharing (UNOS) database for patient data for candidates who received a liver transplant between January 1, 2007 and December 31, 2017. Multivariate Cox proportional hazards regression indicated similar decreases in mortality over time for each race with a decrease in mortality for African Americans: 2010–2012 (HR = .930), 2012–2015 (HR = .882), and 2015–2017 (HR = .883) when compared to 2007–2010. Risk of mortality for African Americans compared to Caucasians varied across the 4 eras: 2007–2010 (HR = 1.083), 2010–2012 (HR = 1.090), 2012–2015 (HR = 1.070), and 2015–2017 (HR = 1.125). While African Americans have seen increases in survival in the past decade, a similar increase in survival for other races leaves a significant survival disparity in African Americans.